UPAYA KONSERVASI INDONESIA ATAS SUMBER DAYA IKAN DI LAUT LEPAS - Muhammad Insan Tarigan (Universitas Lampung, 2015)
The principle of freedom of fishing on the high seas was recognized as one of the principles in customary international law, the Geneva Convention on the High Seas1958, and Part VII of UNCLOS 1982. Regarding to thehigh level of utilization of fish led to the crisis of fishery resources, then the responsible fisheries management becomes a common agenda of the international community. Thisresearch is a normative legal research, data collection was done through studyliterature and documentaries on the primary and secondarylegal materials related to this problem.After conductedthe identification and classification of the data, then data was analysed normatively. There are some international conventions as a basis for maintainingthe conservation of fish on the high seas. UNCLOS 1982, the 1993 FAO Compliance Agreement, the Code of Conduct for Responsible Fisheries (CCRF) in 1995, the IPOA-IUU Fishing, 2001. The result showed thatIndonesia has had several regulations concerning to fisheries, such as Law Number 31 of 2004 concerning to Fisheries and Law Number 45 of 2009 concerning to Fisheries, and the Minister of Marine and Fisheries Regulation Number PER.03/MEN/2009 on Fishing and/or Transporting Fish on the High Seas and the Ministerial Regulation Number Per.12/Men/2012 concerning toEnterprises Capture Fishery on the High Seas. The Government of Indonesia should be able to take advantage of such participation and to improve the exchange of information, data, research fisheries, combating illegal arrests, and other forms of cooperation.Keywords: High Seas, Fish Resources, Indonesia, conservation